Development of national logistics in support of the Serbian Air Force - long-term prospects - Beriša, Hatidža A. (Vojnotehnički glasnik / Military Technical Courier, 2019)
Introduction/purpose: The Air Force accomplishes its tasks in the airspace where it must use special equipment and weapons which makes it extremely technically demanding. This reliance on technique speaks of the importance of logistics in the Air Force. Support to the Air Force of the Serbian Armed Forces is provided by national logistics through, among other things, various branches and parts of industry such as military industry - part of industry that deals with the production and trade of weapons and military equipment. Methods:The methods applied in the paper are the analysis of the tendencies of development of modern aviation assets and military industries in the world as well as the synthesis considering the state of national logistics today and its possibilities of supporting the Serbian Air Force through its basic sources. Results: Basic sources and possible prospects for further development of national logistics are considered, with the focus on the modernization of aircraft and other assets, military personnel training and improvement of their standard of living as well as on the cooperative development of joint projects with foreign partners. Conclusion: It is important to be directed towards creating the conditions for long-term prospects of the development of national logistics in support of the Serbian Air Force.
Keywords: Air Force; Serbian Armed Forces; logistics; armaments; military equipment; situation and prospects